Hexagonal Boron Nitride–Graphene Heterostructures: Synthesis and Interfacial Properties. Issue 1 (6th October 2015) - Li, Qiucheng; Liu, Mengxi; Zhang, Yanfeng; Liu, Zhongfan
Abstract : Research on in‐plane and vertically‐stacked heterostructures of graphene and hexagonal boron nitride (h‐BN) have attracted intense attentions for energy band engineering and device performance optimization of graphene. In this review article, recent advances in the controlled syntheses, interfacial structures, and electronic properties, as well as novel device constructions of h‐BN and graphene heterostructures are highlighted. Firstly, diverse synthesis approaches for in‐plane h‐BN and graphene (h‐BN‐G) heterostructures are reviewed, and their applications in nanoelectronics are briefly introduced. Moreover, the interfacial structures and electronic properties of h‐BN‐G heterojunctions are discussed, and a zigzag type interface is found to preferentially evolve at the linking edge of the two structural analogues. Secondly, several synthetic routes for the vertically‐stacked graphene/h‐BN (G/h‐BN) heterostructures are also reviewed. The role of h‐BN as perfect dielectric layers in promoting the device performance of graphene is presented. Finally, future research directions in the synthesis and application of such heterostructures are discussed. Abstract : In‐plane and vertically stacked heterostructures of graphene and hexagonal boron nitride have attracted intense attention for energy band engineering and device performance optimization of graphene. The synthesis and interfacial properties of both in‐plane (h‐BN‐G) and vertically stacked (G/h‐BN) heterostructures, which should evoke further investigations of the related novel properties, as well as their versatile applications in various aspects, are discussed.